Respostas
respondido por:
3
2^(x)+2^(-x)=a =>
[2^(x)+2^(-x)]^2=a^2 =>
[2^(x)]^2+2.2^(x).2^(-x)+[2^(-x)]^2=a^2 =>
4^(x)+2.1+4^(-x)=a^2 =>
4^(x)+2+4^(-x)=a^2 =>
4^(x)+4^(-x)=a^2-2
O que resulta em “a^2-2”.
(O resultado em função de “a”)
Abraçoss!
[2^(x)+2^(-x)]^2=a^2 =>
[2^(x)]^2+2.2^(x).2^(-x)+[2^(-x)]^2=a^2 =>
4^(x)+2.1+4^(-x)=a^2 =>
4^(x)+2+4^(-x)=a^2 =>
4^(x)+4^(-x)=a^2-2
O que resulta em “a^2-2”.
(O resultado em função de “a”)
Abraçoss!
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás